2021
DOI: 10.1111/jocs.15404
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 3‐day discharge after elective cardiac surgery

Abstract: Background Shorter length of stay (LOS) is a welcome consequence of optimized perioperative care. However, accelerated hospital discharge may have unintended consequences. Before implementing an institutional enhanced recovery after surgery protocol, we evaluated the safety of shorter LOS and compared outcomes of patients with shorter LOS (LOS ≤ 3 days) to those with longer LOS (LOS > 3 days). Methods We identified all patients undergoing elective cardiac surgery with cardiopulmonary bypass between July 2004 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…They found no difference in early mortality or readmission and a lower incidence of POAF and major in-hospital complications in the early discharge group. 16 Other studies have also shown that early discharge after cardiac surgery is not associated with higher readmission. 17,18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no difference in early mortality or readmission and a lower incidence of POAF and major in-hospital complications in the early discharge group. 16 Other studies have also shown that early discharge after cardiac surgery is not associated with higher readmission. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of POAF was lower in the POD1 discharge group, consistent with other fast-track studies. 16,23 One potential criticism of early discharge is that it is difficult to know for sure if patients went into AF after early discharge. This is a fair criticism for subclinical AF, and the only way to accurately assess this would be to use continuous monitoring after discharge, which we feel is not justified given the low rates of POAF in this population.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important risk factors in the development of CPSP is postoperative acute pain intensity level (Katz & Seltzer, 2009;Schug & Bruce, 2017). With people having shorter hospital stays after cardiac surgery (Son et al, 2021), acute pain becomes a problem to address at home during recovery. Surprisingly, a lack of studies documenting pain after discharge from hospital has been observed (Park et al, 2020), thus reflecting a gap in postoperative pain management and the need to increase our efforts in understanding the experience of postoperative pain and the potential of efficacy of interventions in this phase of the postoperative continuum.…”
Section: Timing Of Interventionsmentioning
confidence: 99%
“…Cardiac surgeries became frequent surgical procedures (Virani et al, 2021) with reduced length of stay in hospitals (Engelman et al, 2019;Son et al, 2021). However, postoperative persistent pain or chronic post-surgical pain (CPSP) after cardiac surgery, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A behavioral intervention targeting known risk factors during the sensitive, subacute recovery period may prevent CPSP development [ 16 , 22 , 23 ]. With reduced hospital length of stay after cardiac surgery [ 24 , 25 ], patients are at risk for CPSP and prolonged opioid use [ 26 , 27 ] as they become more isolated with relatively elevated levels of pain after discharge [ 3 , 28 , 29 ]. Moreover, rarely aware of the risk of CPSP [ 30 ], patients may seek pain management support only after their pain has become chronic and disability has already surfaced [ 31 ].…”
Section: Introductionmentioning
confidence: 99%